Web-Based Digital Library Information System in Kotaraja Village - Muhammad Zamroni Uska; Yosi Nur Kholisho; Rasyid Hardi Wirasasmita; Jamaludin Jamaludin (JOURNAL OF INFORMATICS AND TELECOMMUNICATION ENGINEERING, 2023)
Libraries as managers of information and knowledge must be able to use and utilize information technology optimally to meet various needs. However, the library in Kotarajara village has several obstacles including difficulties in finding the desired book, frequent loss of books due to data recording loan transactions are not managed properly, and the management of borrowing and returning books is still done manually, which is still done by writing on the book. This research aims to produce a web-based Kotaraja village library information system, and find out the feasibility and quality of the library information system. The model used in this study is Research and Development with the Waterfall method. Information system testing in this study uses the ISO 25010 standard which consists of 3 aspects, namely functionality, usability, and efficiency. The subjects in this study amounted to 10 people. Data collection techniques use questionnaires, while data analysis uses quantitative descriptive. The results showed that the information system developed based on the feasibility results of material experts amounted to 88.9% of the very feasible category, the results of the IT expert feasibility test obtained 82.3% of the very feasible category, and the results of user response of 81.2% of the very good category and the efficiency aspect of 91% grade B. Thus, it can be concluded that this application is feasible to be used as a web-based Kotaraja village library information system.